2015
DOI: 10.1037/a0038783
|View full text |Cite
|
Sign up to set email alerts
|

Weep and get more: When and why sadness expression is effective in negotiations.

Abstract: Although recently some research has been accumulated on emotional expressions in negotiations, there is little research on whether expressing sadness could have any effect in negotiations. We propose that sadness expressions can increase the expressers' ability to claim value in negotiations because they make recipients experience greater other-concern for the expresser. However, only when the social situation provides recipients with reasons to experience concern for the expresser in the first place, will rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 128 publications
1
32
0
Order By: Relevance
“…Sadness has received attention in negotiation research. In one study, displays of sadness led to greater concessions from the other side, presumably because the latter felt concern for the person displaying sadness (Sinaceur et al, 2015). In one of their experiments, Sinaceur et al (2015) examined the interaction between the emotion displayed (anger or sadness) and the appropriateness of the emotion.…”
Section: Characteristics Of the Contextmentioning
confidence: 99%
“…Sadness has received attention in negotiation research. In one study, displays of sadness led to greater concessions from the other side, presumably because the latter felt concern for the person displaying sadness (Sinaceur et al, 2015). In one of their experiments, Sinaceur et al (2015) examined the interaction between the emotion displayed (anger or sadness) and the appropriateness of the emotion.…”
Section: Characteristics Of the Contextmentioning
confidence: 99%
“…In vengeful interactions, opponents' displays of sadness could decrease revenge seeking by inducing a greater concern for the antagonist's welfare in the observer. Supportive of this hypothesis, a study showed that negotiators conceded more to interaction partners who expressed sadness, especially if they felt responsible for the other's feeling (Sinaceur, Kopelman, Vasiljevic, & Haag, 2015). Thus, one could hypothesize contrary effects of sad and angry expressions on revenge seeking for interactions in which the person has high power and can risk further escalation of aggression.…”
mentioning
confidence: 99%
“…Finally, given the degree to which technology is present in our daily lives, it is imperative to explore the plethora of discrete emotions relevant to negotiation. Not only anger and happiness but also less studied emotions such as anxiety (Brooks & Schweitzer, 2011;Rosette, Kopelman, & Abbott, 2014) and sadness (Sinaceur, Kopelman, Vasiljevic, & Haag, 2015) are relevant to understanding cross-cultural communication via information technology. Future research will help understand whether, and to what degree and intensity, expression of discrete emotion is considered culturally appropriate when communicated face-to-face and via information technology.…”
Section: The Increasing (And Potentially Problematic) Role Of Technologymentioning
confidence: 99%